Pengaruh Model Pembelajaran Berbasis Masalah Terhadap Hasil Belajar Siswa Pada Materi Ekosistem Di Kelas X SMA Negeri 2 Tondano - Regina Indri Rembang; Alfonds A. Maramis; Fanny Nanlohy (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The first step in the problem-based learning model is to expose pupils to actual or simulated challenges. When presented with this topic, students will understand that in order to solve it, they will need to apply critical thinking techniques, take a methodical approach, and integrate data from several scientific disciplines. Through student observations in the school environment, particularly the school garden, this experimental study seeks to ascertain the impact of the problem-based learning model (PBM) on student learning outcomes in ecosystem content in class X SMA Negeri 2 Tondano. A pretest-posttest control group design was employed in the study procedure. Sixty people were randomly selected from each of the two courses; the experimental class was treated using a problem-based learning model, while the control class was treated using a traditional learning model. Tests with objectives are employed as tools. Testing the normalcy and homogeneity tests—two criteria for data analysis—comes first and is followed by hypothesis testing. The study's findings revealed that the experimental class's average learning outcome was 98.16, while the control class's average learning outcome was 81.63. As a result, student learning outcomes can be enhanced by the problem-based learning model (PBM).